Engaging men in supporting maternal and child consumption of milk and other animal source foods in Rwanda: A facilitator’s guide - Colverson, Kathleen E. (International Livestock Research Institute, 2021)
The guide is organized by a series of sessions. The sessions have been developed with a Training of Trainers (TOT) focus to encourage a multiplier effect with participants sharing the knowledge and skills within their individual organizations and communities they work in. The current training has been developed to be conducted virtually, however, the PowerPoint slides - https://hdl.handle.net/10568/113693 provide directions for both in-person and virtual workshops. Both in-person and virtual agendas are included in this guide.